2013
DOI: 10.1002/jgrd.50549
|View full text |Cite
|
Sign up to set email alerts
|

Optical studies of rocket exhaust trails and artificial noctilucent clouds produced by Soyuz rocket launches

Abstract: [1] Detailed tracing of an exhaust plume from a rocket's initial trajectory is a scientifically and diagnostically useful technique. It can provide detailed information on the atmosphere's mean winds, wind shears, turbulent regime, and physical state over a wide altitude range from 50 to 200 km. We analyze Soyuz rocket exhaust plumes from Plesetsk on 21 May 2009 and 27 June 2011, which uncovered significantly different atmospheric states and underlying dynamics. The first case showed highly dynamical condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 39 publications
1
6
0
Order By: Relevance
“…Modeling this effect, however, requires a model with very fine spatial grid size to account for the supersonic waves initiated by the rocket itself as the moving object. Additionally, the ballon‐shaped contrails (or gasdynamic holes) seen in optical imager around turbopause resulting from collisional shocks in the rocket wake [ Platov and Kosch , ; Platov et al ., ; Molchanov and Platov , ; Dalin et al ., ] were not adequately reproduced in our model in comparison to imager observations. It is possibly that our assumptions of artificial viscosity and model grid size are insufficient to capture the effects of colliding shocks in the rocket wake.…”
Section: Discussionsupporting
confidence: 90%
“…Modeling this effect, however, requires a model with very fine spatial grid size to account for the supersonic waves initiated by the rocket itself as the moving object. Additionally, the ballon‐shaped contrails (or gasdynamic holes) seen in optical imager around turbopause resulting from collisional shocks in the rocket wake [ Platov and Kosch , ; Platov et al ., ; Molchanov and Platov , ; Dalin et al ., ] were not adequately reproduced in our model in comparison to imager observations. It is possibly that our assumptions of artificial viscosity and model grid size are insufficient to capture the effects of colliding shocks in the rocket wake.…”
Section: Discussionsupporting
confidence: 90%
“…Verification of the results with other measurements from the same altitude range would be useful. The available measurements are limited, but the analysis of rocket exhaust trails [see, e.g., Meier et al , ; Dalin et al , ] offers the potential for further analysis of turbulence dynamics in this region. The rocket exhaust trails are long‐lived and provide extended observations that extend to even higher altitudes.…”
Section: Resultsmentioning
confidence: 99%
“…Baumgarten et al [2012] found that NLCs can behave like a passive tracer for about an hour and are blown downstream several hundred kilometers. Dalin et al [2013b] showed that artificial NLCs induced by rocket exhaust traveled from Plesetsk via Denmark to UK for 9 h. Wave streaks or bands can move by a speed of tens to hundreds meters per second depending on the wavelengths, resulting in rapid local variations in the cloud brightness [e.g., Witt, 1962;Fogle and Haurwitz, 1966]. A unique combination of the physics exists behind each cloud structure and therefore some degree of randomness is perceived in these variations.…”
Section: Introductionmentioning
confidence: 99%